Ultrasound Measurement of Thyroid Isthmus Thickness in Clinically Euthyroid Subjects - Kayastha, Prakash; Paudel, Sharma; Ghimire, Ram Kumar (Nepalese Journal of Radiology, 2018)
Introduction: The purpose of this study was to establish the reference value of normal thickness of thyroid isthmus among clinically euthyroid Nepalese individuals using Ultrasonography and correlate this with thyroid volume, sex, individual’s built and geographic location. Methods: This was a prospective cross sectional study involving 485 clinically euthyroid individuals. B -mode Ultrasonography was used to measure the thickness of thyroid isthmus in transverse plane. Mean thickness of isthmus for male and female was obtained and Pearson correlation test was used to see the relationship with various factors. Results: Among 485 individuals between 1 to 83 years of age, 221 were males and 264 were females. Maximum individuals (72.99%) were from hilly region and minimum (3.30%) were from Himalayan region. Mean thickness of isthmus was 3.097 ± 1.009 mm (range 1.0 to 6.8 mm). It was 3.114 ± 0.9513 mm for male and 3.083 ± 1.056 mm for female. Isthmus thickness best correlated with total thyroid volume (r=0.373, p=0.0001). Isthmus thickness also positively correlated with body mass index (r=0.355, p =0.0001), body surface area (r= 0.296, p=0.0001), weight (r =0.334, p=0.0001) and height (r =0.130, p =0.004) of the individuals. Conclusion: This study estimated the normal reference value of thyroid isthmus thickness. As isthmus thickness correlated well with total thyroid volume, it can roughly guide the thyroid volume and help assessment of thyroid size in diffuse thyroid disease.